Phytosterol Esterification is Markedly Decreased in Preterm Infants Receiving Routine Parenteral Nutrition. Issue 12 (24th September 2016) - Savini, Sara; Correani, Alessio; Pupillo, Daniele; D'Ascenzo, Rita; Biagetti, Chiara; Pompilio, Adriana; Simonato, Manuela; Verlato, Giovanna; Cogo, Paola; Taus, Marina; Nicolai, Albano; Carnielli, Virgilio Paolo
Abstract: Several studies reported the association between total plasma phytosterol concentrations and the parenteral nutrition‐associated cholestasis (PNAC). To date, no data are available on phytosterol esterification in animals and in humans during parenteral nutrition (PN). We measured free and esterified sterols (cholesterol, campesterol, stigmasterol, and sitosterol) plasma concentrations during PN in 16 preterm infants (500–1249 g of birth weight; Preterm‐PN), in 11 term infants (Term‐PN) and in 12 adults (Adult‐PN). Gas chromatography–mass spectrometry was used for measurements. Plasma concentrations of free cholesterol (Free‐CHO), free phytosterols (Free‐PHY) and esterified phytosterols (Ester‐PHY) were not different among the three PN groups. Esterified cholesterol (Ester‐CHO) was statistically lower in Preterm‐PN than Adult‐PN. Preterm‐PN had significantly higher Free‐CHO/Ester‐CHO and Free‐PHY/Ester‐PHY ratios than Adult‐PN (Free‐CHO/Ester‐CHO: 1.1 ± 0.7 vs. 0.6 ± 0.2; Free‐PHY/Ester‐PHY: 4.1 ± 2.6 vs. 1.3 ± 0.8; *P < 0.05). Free‐CHO/Ester‐CHO and Free‐PHY/Ester‐PHY ratios of Term‐PN (Free‐CHO/Ester‐CHO: 1.1 ± 0.4; Free‐PHY/Ester‐PHY: 2.9 ± 1.7) were not different from either Preterm‐PN or from Adult‐PN. Plasma Free‐CHO/Ester‐CHO and Free‐PHY/Ester‐PHY were unchanged after 24 h on fat‐free PN both in Preterm‐PN and in Adult‐PN. Free‐PHY/Ester‐PHY did not correlate with phytosterol intake in Preterm‐PN. Free‐PHY/Ester‐PHY of Preterm‐PN was positively correlated with the Free‐CHO/Ester‐CHO and negatively correlated with gestational age and birth weight. In conclusion, PHY were esterified to a lesser extent than CHO in all study groups; the esterification was markedly decreased in Preterm‐PN compared to Adult‐PN. The clinical consequences of these findings warrant further investigations.